2021
DOI: 10.3389/fphar.2021.700373
|View full text |Cite
|
Sign up to set email alerts
|

PTEN Methylation Promotes Inflammation and Activation of Fibroblast-Like Synoviocytes in Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is characterized by a tumor-like expansion of the synovium and subsequent destruction of adjacent articular cartilage and bone. In our previous work we showed that phosphatase and tension homolog deleted on chromosome 10 (PTEN) contributes to the activation of fibroblast-like synoviocytes (FLS) in adjuvant-induced arthritis (AIA), but the underlying mechanism is not unknown. In this study, we show that PTEN is downregulated while DNA methyltransferase (DNMT)1 is upregulated in FLS fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…Overexpression of PTEN can significantly reduce the expression of pro-inflammatory factors, chemokines, vascular cell adhesion factor-1, and vascular endothelial growth factor-a in AIA experimental animals. Consistent with the previous, the expression of PTEN is regulated by DNA methylation and is accompanied by changes in the AKT signal (22), and the methylation of PTEN has been shown to promote inflammation and activation of RA fibroblast-like synoviocyte (FLS) (23). Shikonin significantly reduces angiogenesis in RA.…”
Section: The Potential Connection Between Dna Methylation Of Cd4+ T C...supporting
confidence: 81%
“…Overexpression of PTEN can significantly reduce the expression of pro-inflammatory factors, chemokines, vascular cell adhesion factor-1, and vascular endothelial growth factor-a in AIA experimental animals. Consistent with the previous, the expression of PTEN is regulated by DNA methylation and is accompanied by changes in the AKT signal (22), and the methylation of PTEN has been shown to promote inflammation and activation of RA fibroblast-like synoviocyte (FLS) (23). Shikonin significantly reduces angiogenesis in RA.…”
Section: The Potential Connection Between Dna Methylation Of Cd4+ T C...supporting
confidence: 81%
“…Similar to our findings, Xu et al confirmed that the m6A modification-related PI3K/Akt pathway modulated by methylase METTL14 through PTEN had an effect on HDAC5-induced EMT in renal tubular cells exposed to high glucose (HG) treatment [ 40 ]. DNMT1 could downregulate PTEN, while PTEN overexpression reduced inflammation and activated fibroblast-like synoviocytes via AKT signaling in rheumatoid arthritis [ 41 ]. Moreover, our results indicated that the PI3K/Akt inhibitor LY294002 attenuated PTEN downregulation-induced EMT and NF-κB activation, thereby demonstrating that activation of the PI3K/Akt pathway in response to PTEN loss could result in the activation of the downstream proinflammatory NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…On this point, lactate could compensate the inflammatory setting triggered by hypoxic condition, promoting a metabolic switch from inflammatory macrophage to homeostatic M2 like-polarization by epigenetic modifications (histone lactylation) [ 95 ]. Methylation also promotes inflammation and activation of fibroblast-like synoviocytes in RA [ 228 , 229 ] as well as is associated with the level of transcript in T lymphocytes from RA patients [ 230 ]. Notably, differential DNA methylation correlates with response to methotrexate in RA PBMCs [ 231 , 232 ].…”
Section: Interplay Between Mitochondrial and Epigenetic Mechanisms In Ramentioning
confidence: 99%